Políticas públicas, turismo e unidades de conservação municipais: uma experiência em Cancão, Serra do Navio, Amapá - ALBERTO, Diana Priscila Sá (2010)
This work, entitled "Public policies, tourism and municipal conservation units: an experience in Cancao, Serra do Navio, Amapa" deals with the issue of public policy for tourism and environment, focusing on discussion of new categories of study which are the units of conservation municipal (UCM), dealing with the Municipal Natural Park of the song, and highlights a brief analysis of the social-cultural city, which was the first city-company mineral exploration in the Amazon. The objective of this research is to analyze the dynamics of tourism and environmental management, focused on the UCM in the municipality of Serra do Navio, emphasizing well as being the issue is socio-cultural city, from a context that was once a company. The methodology of the work consisted of literature and documents in Belem /PA and Macapa / AP; field research in the city of Serra do Navio, using interviews and questionnaires with the municipal and state governments, private sector, and the community at large, doing well, visual record of the residents of the locality and finally the data analysis, quantitative and qualitative, from the collection field. Preliminary results indicate that tourism is gradually inserting itself in the city, and encouraged by the state government and also municipal, and environmental issues is a significant issue for the town as it is has one of the first places to feature UCM northern Brazil, and finally, that the company still has a mountain great memory about the experiences of the former mining.